IMPLEMENTATION OF INCLUSIVE EDUCATION: OPPORTUNITIES AND BARRIERS IN THE LOCAL CONTEXT - Sutomo, Moh.; Lestari, Maghfirotul Firmaning; Ubaidillah, Sofwan Roif (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Inclusive education aims to provide equal access to education for all students, including those with special needs, in a friendly and supportive learning environment. This study was conducted at SDS Ulul Albab, Jember Regency, with the aim of analyzing opportunities and barriers in the implementation of inclusive education in one particular local context. The research approach used was qualitative with a case study method. Data were collected through in-depth interviews, participant observation, and document analysis from schools that implement the inclusive education model. The results of the study indicate that the main opportunities in the implementation of inclusive education include government policy support, teacher commitment, and community participation. However, significant obstacles were also found, such as the lack of facilities that support the needs of students with special needs, limited teacher competence, and the existence of social stigma against inclusive students. This study concludes that the implementation of inclusive education requires a collaborative approach between the government, schools, and the community to overcome obstacles and maximize opportunities. These findings provide practical recommendations for stakeholders to improve the effectiveness of inclusive education at the local level.